Еще раз о достоверности оценок характеристик неопределенности и погрешности измерений - Данилов, А. А.; Захаров, И. П. (Харківський університет повітряних вил, 2015)
A comparison of the accuracy of estimates of the characteristics of uncertainties and errors of measurement was realized. The Monte Carlo simulation was taken as a reference method of evaluation. The obtained results are illustrated by the simple example.
Once again about the reliability of the estimates uncertainties and errors of measurement
Keywords: characteristics of error; measurement uncertainty; coverage factor